Pandemic Policymaking in Presidential Federations: Explaining Subnational Responses to Covid-19 in Brazil, Mexico, and the United States. Issue 4 (14th August 2021) - Bennouna, Cyril; Giraudy, Agustina; Moncada, Eduardo; Rios, Eva; Snyder, Richard; Testa, Paul
Abstract: Why do COVID-19 social distancing policies vary so widely across states in federal countries? This mixed-methods study of Brazil, Mexico, and the United States finds that state-level variation in the stringency of social distancing policies is driven not by the epidemiological, demographic, or socioeconomic factors commonly emphasized in previous research, but largely by political factors. Introducing a novel framework for explaining pandemic policymaking, the study shows the central importance of political parties, presidential power, and governors' coalitions in determining state-level policy stringency. In the United States and Mexico, statistical and qualitative evidence indicates that interstate collaboration among governors, combined with top-down pressures from national party elites and presidents, led to greater policy alignment among coordinated states. In Brazil, in contrast, where there is little evidence of either policy coordination or alignment, state-level policies resulted instead from intrastate factors and diffusion. Together, these findings highlight how a multilevel framework attuned to varied combinations of intra-unit, cross-unit, and cross-level causal factors strengthens our understanding of pandemic policymaking.